Pengaruh PAD dan Angkatan Kerja Terhadap IPM Di Provinsi Kalimantan Selatan Tahun 2015-2019 - Atika Nurhabibah; Arfida Boedirochminarni; Novi Primita Sari (Program Studi Ekonomi Pembangunan, 2022)
The purpose of this study is to analyze the effect of local original income, number of generations, gross regional domestic product on the human development index in the district of South Kalimantan province from 2015-2019. The research method used is panel data by taking secondary data and the analytical tools used are panel data regression, classical assumption test, and hypothesis testing. The results of this study are partially local revenue, the number of labor force, and gross regional domestic product have a positive and significant effect on the human development index in the district of South Kalimantan province. And simultaneously Regional Original Income, Total Labor Force, and Gross Regional Domestic Product have a significant effect on the human development index in the district of South Kalimantan province.